States, Banks and the Financing of the Economy: Monetary Policy and Regulatory Perspectives - Morten Balling; Patricia Jackson; Ernest Gnan; Jean-Pierre Danthine; Jean-Charles Rochet; Lorenzo Bini Smaghi; Thorvald Grung Moe; Malgorzata Pawlowska; Jerzy Marzec; Andrew R. Gimber; Alex Cukierman; Edward J. Kane; et al. (SUERF - The European Money and Finance Forum, 2013)
On 5-6 September 2012 SUERF held its 30th Colloquium “States, Banks, and the Financing of the Economy” at the University of Zürich, Switzerland. The papers included in this SUERF Study are based on contributions to the Colloquium. All the papers in this publication discuss from different angles the complex interrelations between states and financial systems, which have developed in recent years with economic, financial and sovereign debt crises. The contributions look primarily on the monetary policy and financial regulation and supervision perspectives. In the preceding SUERF Study (2013/2), the focus of the contributions also delivered at the 30th SUERF Colloquium is on fiscal policy and sovereign debt perspectives.
Keywords: E30; E43; E5; E52; B31; E52; E58; E63; N12; C32; D22; D50; G21; G28; G33; E5; E58; E5; E58; G21; G33; 330; financial crisis; procyclicality; counter cyclical balances; financial cycle; liquidity; repo markets; money; banking; monetary union; unusual monetary policy; Marriner Eccles; Central Banking; Monetary Policy; Fiscal Policy; trade credit; substitution hypothesis; credit rationing; bank resolution; bailouts; Central bank independence; shadow banking; regulation; supervision; macroprudential regulation; Central bank policymaking; crisis management; bail-outs; supervision; financial management; Bail-in; bank resolution; bridge banks; capital allocation; Pigovian tax; resource allocation; Geldpolitik; Geldpolitische Transmission; Zentralbankunabhängigkeit; Bankenregulierung; Welt